Efektivitas Model Pembelajaran Pemecahan Masalah Berbantuan GeoGebra terhadap Kemampuan Pemecahan Masalah Matematika - Wibowo, Wahyu Ari; Tarso, Tarso; Siswanto, Deny Hadi (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2026)
This study aims to examine the effect of the Problem-Solving learning model assisted by GeoGebra on students' mathematical problem-solving abilities. The research design employed was the Posttest Only Control Group Design, which allows for the evaluation of treatment effectiveness by comparing the experimental group with the control group.The population of the study consisted of all eighth-grade students of Muhammadiyah 1 Mlati Junior High School, totaling 60 students. Sampling was conducted using a saturated sampling technique, where the entire population was included as the research sample, with class VIII A serving as the experimental group and VIII B as the control group. Research data were collected through tests designed to measure students' mathematical problem-solving skills. Prior to the research, the test instrument was validated and tested for reliability with class IX A students of Muhammadiyah 1 Mlati Junior High School. The results revealed that the Problem-Solving learning model assisted by GeoGebra had a positive and significant effect on students' mathematical problem-solving abilities. This was evident from the higher test scores of students in the experimental group compared to those in the control group. These findings indicate that the use of GeoGebra as a teaching medium helps students understand mathematical concepts in a visual, interactive, and effective manner. Therefore, the Problem-Solving learning model assisted by GeoGebra can be considered an alternative teaching strategy to optimize students' problem-solving skills in mathematics.